Factors Influencing Employment Opportunities with Salary for People with Disabilities - Thi Mo, Nguyen (International Review of Management and Marketing, 2024)
People with disabilities (PWDs) are considered one of the largest and most vulnerable communities, easily affected and harmed. As of December 1, 2022, Vietnam has over 7 million PWDs, accounting for more than 7.06% of the population aged 2 and older, with severe and extremely severe disabilities accounting for about 28.9%. Recent domestic studies have focused on creating capital and building working conditions for PWDs. However, there are still many limitations in terms of effectiveness. The number of unemployed PWDs tends to increase, amidst the general difficulties of the economy. The aim of this article is to clarify the factors influencing the employment opportunities with salary for people with disabilities after the Covid-19 pandemic. The authors directly collected data from 225 employed and unemployed PWDs in two major cities, Hanoi and Ho Chi Minh City, from September 2023 to December 2023 through interview methods. Using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique on SPSS 20 and AMOS 20 software, the results show that factors strongly influencing employment opportunities for PWDs include their level of education and participation in organizations and employment support programs. The study contributes to understanding and implications for policymakers and labor users.